Preparation method of antireflection glass coated on surface of tin layer
By using a flow tank in the coating process to control the flow rate and pressure difference of the sol gel, combined with infrared radiation and hot air circulation technology, the coating thickness and wear resistance problems are solved, and the transmission ratio and wear resistance of the glass are improved. sex.
Patent Information
- Application Number
- CN202411163193.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing coating process cannot effectively control the thickness and quality of the coating applied to the glass substrate surface, resulting in the hardness and wear resistance of the coating being unable to be guaranteed.
By designing the flow tank, the flow rate and pressure difference of the sol gel are controlled to ensure the uniform distribution and thickness of the coating on the glass substrate, and cured with infrared radiation and hot air circulation technology to form a thin film with hardness and wear resistance layer.
The uniformity and hardness of the coating are achieved, the transmission ratio and wear resistance of the glass are improved, and the quality and service life of the coating are ensured.
Smart Images

Figure CN119161111A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass production, in particular to a method for preparing anti-reflection glass coated on the surface of a tin layer. Background Art
[0002] Ordinary glass is a flat glass formed by rolling the glass liquid along a tin liquid tank through multiple angled smooth high-resistance rollers at an appropriate viscosity. During the production process, the tin liquid and the high-temperature glass liquid also undergo certain chemical and physical reactions on the lower surface of the glass, forming a solid film. Its characteristics are good thickness uniformity, smooth surface, small roughness, high density, and no surface cracks. However, the transmittance is low at only 88.5%, the yield is high, and the price is relatively cheap. A layer of sol-gel material with silicon dioxide (SiO2) and titanium dioxide (TiO2) as the main materials is coated on the glass with a smooth surface and a tin layer to increase its transmittance and improve the hardness and wear resistance of the surface.
[0003] The existing coating is generally formed by a roller coating process, during which the material is deposited from the storage tank onto the application roller. The scraper blade of the scraper roller is used to control the thickness of the coating placed on the application roller, and the sol material is evenly coated on the substrate through a conveying device. Because the existing roller coating process can only control the thickness of the coating by the scraper blade, the coating speed and quality of the coating on the surface of the glass substrate cannot be guaranteed, so the hardness and wear resistance of the coating on the glass substrate cannot be guaranteed. Therefore, a method for preparing anti-reflective glass coated on the surface of a tin layer is provided, and by controlling the coating speed and pressure of the coating, the formed coating meets the hardness and wear resistance requirements. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing anti-reflection glass coated on the surface of a tin layer, wherein the coating speed of the sol layer is controlled by a liquid flow trough, the coating thickness is ensured, the quality of the coating is further improved, and the coating has a certain hardness and wear resistance, which meets the use requirements.
[0005] The present invention provides the following technical solution: a method for preparing anti-reflection glass coated on the surface of a tin layer,
[0006] The steps for preparing the anti-reflection glass coated with a tin layer are as follows:
[0007] S1, tin layer glass is put on, inspected and cleaned, and surface defects are detected;
[0008] S2, preheating the tin layer glass substrate;
[0009] S3, sol-gel coating;
[0010] S4, subjecting the sol-gel coated on the surface of the glass substrate to surface tension shrinkage;
[0011] S5, curing the sol-gel by infrared radiation or hot air circulation;
[0012] S6, cooling and waste discharge;
[0013] S7, turning the glass substrate 180°;
[0014] S8, glazing the surface of the glass substrate;
[0015] S9, tempering, quenching, cleaning and drying the glass substrate;
[0016] After being ground, cleaned and dried, the glass substrate enters a preheating device, and the glass substrate is sent to a combined roller coating device with a liquid flow trough, and the sol-gel solution is evenly coated on the glass substrate, and the glass substrate passes through a conveying area and a curing area to form a solid film layer with a porous structure and a dense surface;
[0017] The flow tank is formed with a gel storage tank and a discharge tank, the bottom area of the gel storage tank is larger than the bottom area of the discharge tank, and the thickness of the sol-gel layer on the glass substrate is determined by the discharge rate of the fluid in the flow tank;
[0018] Discharge flow rate V = Q / Lh, Q is the flow rate of sol-gel per unit time, L is the length of the tank, and h is the height of the tank;
[0019] Flow rate Q = LΔPh 3 / 12wμ, L is the slot length, ΔP is the pressure difference across the slot width, ΔP=P1-P0, h is the slot height, w is the slot width, and μ is the viscosity of the coating;
[0020] The length of the inflow section between the parallel surfaces is calculated by the Braus approximation method, that is, the slot length L = hReH / 100, where h is the slot height, H is the fluid pressure head height, and Re is the Reynolds number of the coating fluid;
[0021] The flow rate of the coating will also affect the internal pressure of the flow tank. If the flow rate is too high, the coating will not be able to fill the flow tank, so that the coating cannot be evenly distributed in the flow tank; if the flow rate is too low, the flow tank will be completely filled with coating, resulting in uneven flow rate and excessive back pressure. Therefore, the pressure difference between the glue tank and the discharge tank will affect the quality and uniformity of the coating.
[0022] The pressure in the flow tank includes the pressure P0 on the surface of the sol-gel solution, the pressure P1 at the inlet to the discharge tank, and the pressure P2 at the outlet of the discharge tank. The pressure is also related to the fluid pressure head height H.
[0023] AP=P1-P2,ΔP=ρgH+P0,because the pressure P0 on the surface of sol-gel solution is atmospheric pressure,therefore,
[0024]
[0025] Based on the above parameters and calculations, for sol-gel coatings, the groove height is between 0.05 and 1.0 mm.
[0026] Preferably, the groove height is between 0.1 and 0.3 mm.
[0027] To achieve a coating thickness that matches the resulting final dry film thickness, the wet thickness of the coating controls the final cured film thickness, which is affected by the final dry film thickness, the solids content of the coating, and the target porosity of the final dried film;
[0028] Wet thickness
[0029] In the above formula, DT is the final dry film thickness, which is controlled at 80-180nm, SC is the solid content of the coating, which is between 1% and 4.2%, and P is the target porosity, which is between 20-40%.
[0030] The hardness of the final dry film is between 3H and 6H in pencil hardness.
[0031] The final dry film can perform an abrasion test 50 times according to the specification EN1096-2 method without losing 0.5% of the absolute transmittance loss measured by a spectrophotometer, and no marks after friction will be produced on the surface of the final dry film under 1000 Lux lighting conditions. At the same time, after the glass substrate is flipped 180°, the surface of the final dry film will not be affected by the transmission device.
[0032] The thickness of the final dry film is between 120 nm and 150 nm.
[0033] In order to preheat the glass substrate, in S2, the hot air circulation device blows 30-50℃ hot air evenly to the glass surface through 3-8 groups of wind knives or 3-9 infrared heating systems with gold-plated layers through the 2.7-4.5μm band, and dries and heats the glass substrate to 25-28℃ based on the principle of thermal radiation. The temperature of the substrate needs to supplement the heat of the elastic roller made of polyurethane with a surface hardness of 35-38 to increase the elasticity of the rubber roller.
[0034] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0035] (1) By designing a flow trough, the flow rate of the sol is ensured by using various size parameters of the flow trough, and the coating thickness of the coating on the glass substrate is controlled by the flow rate of the sol;
[0036] (2) The target wet thickness of the coating can be obtained by the final dry film thickness, the solid content of the coating, and the target porosity of the final dry film, that is, the required coating thickness can be obtained so that the thickness of the sol layer coated on the glass substrate through the flow tank can match the required coating thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0038] Figure 1 It is a schematic structural diagram of the liquid flow tank of the present invention;
[0039] Figure 2 is a schematic diagram of a spectrum curve of the glass substrate of the present invention;
[0040] Figure 3 and Figure 4 is a plot of the relationship between the logarithmic ratio of the Planck curve and the radiation power and wavelength of the present invention;
[0041] Figure 5 is a graph of the maximum curing temperature versus final film thickness, refractive index, and water contact angle;
[0042] Figure 6 This is the electron mirror scan structure diagram of the final film;
[0043] In the figure: 1, liquid flow trough; 11, gel storage trough; 110, fluid pressure head height; 111, trough height; 112, trough width; 113, pressure at the inlet of the discharge trough; 114, pressure on the surface of the sol-gel solution; 115, pressure at the outlet of the discharge trough; 12, discharge trough. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example
[0046] See also Figure 1 The present invention provides a technical solution: a method for preparing anti-reflection glass coated on the surface of a tin layer, and the steps for preparing the glass coated with the tin layer are as follows:
[0047] S1, tin layer glass is put on, inspected and cleaned, and surface defects are detected;
[0048] S2, preheating the tin layer glass substrate;
[0049] S3, sol-gel coating;
[0050] S4, subjecting the sol-gel coated on the surface of the glass substrate to surface tension shrinkage;
[0051] S5, curing the sol-gel by infrared radiation or hot air circulation;
[0052] S6, cooling and waste discharge;
[0053] S7, turning the glass substrate 180°;
[0054] S8, glazing the surface of the glass substrate;
[0055] S9, tempering, quenching, cleaning and drying the glass substrate;
[0056] After being ground, cleaned and dried, the glass substrate enters the preheating device, and is sent to the combined roller coating device with a liquid flow trough 1 by horizontal or vertical transmission. The sol-gel solution is evenly coated on the glass substrate, so that the glass substrate with the coating on the surface passes through the transmission area and the curing area to form a solid film layer with a dense surface containing a porous structure. The sol-gel solution is a solution mixed with alcohol or isopropanol with SiO2+TiO2 as the main components. The transmission area is an area that shrinks the surface tension of the liquid, and the curing area is an area with infrared radiation and hot air circulation devices. The surface tension of the coating is shrunk by the transmission area, and the coating is cured by the curing area. The solid film layer has a certain hardness, wear resistance and adhesion, and is fused together by high-temperature sintering, and has higher hardness, wear resistance and transmittance, and the gain is increased by about 2.0-2.2%;
[0057] like Figure 1 As shown, a gel containing groove 11 and a discharge groove 12 are formed in the flow groove 1, the bottom area of the gel containing groove 11 is larger than the bottom area of the discharge groove 12, and the thickness of the sol-gel layer on the glass substrate is determined by the discharge rate of the fluid in the flow groove 1, and the discharge rate is related to the groove length, groove width 112, groove height 111 of the flow groove 1, and the viscosity and density of the coating;
[0058] In one embodiment, the fluid in the flow tank 1 is double-layered and has a fully formed velocity distribution when leaving the distribution blade. The laminar flow in the tank can be achieved by ensuring that the fluid has a Reynolds number less than 1400; in one embodiment, the Reynolds number (Re) of the coating fluid in the tank is less than 100, and the coating fluid can leave the tank at a certain velocity distribution, which is independent of the slight edge effects, turbulence and other disturbances existing on the coating fluid entering the tank. This condition can be achieved by ensuring that the tank width 112 is significantly longer than the length of the inlet section;
[0059] The discharge flow rate V = Q / Lh, Q is the flow rate of sol-gel per unit time, L is the length of the tank, and h is the height of the tank 111;
[0060] Flow rate Q = LΔPh 3 / 12wμ, L is the slot length, h is the slot height 111, w is the slot width 112, ΔP is the pressure difference across the slot width 112, ΔP = P1-P0 = ρgH+P0, μ is the viscosity of the coating;
[0061] The length of the inlet section between the parallel surfaces is calculated by the Braus approximation method, that is, the slot length L = hReH / 100, where h is the slot height 111, H is the fluid pressure head height 110, and Re is the Reynolds number of the coating fluid.
[0062] The flow rate of the coating will also affect the internal pressure of the flow tank 1. If the flow rate is too high, the coating will not be able to fill the flow tank 1, so that the coating cannot be evenly distributed in the flow tank 1; if the flow rate is too low, the flow tank 1 will be completely filled with coating, resulting in uneven flow rate and excessive back pressure. Therefore, the pressure difference between the glue tank 11 and the discharge tank 12 will affect the quality and uniformity of the coating.
[0063] The pressure in the flow tank 1 includes the pressure 114P0 on the surface of the sol-gel solution, the pressure 113P1 at the inlet to the discharge tank 12, and the pressure 115P2 at the outlet of the discharge tank 12. The pressure is also related to the fluid pressure head height 110H.
[0064] AP=P1-P2,ΔP=ρgH+P0,because the pressure 114P0 on the surface of sol-gel solution is atmospheric pressure,therefore,
[0065]
[0066] Based on the above parameters and calculations, for sol-gel coatings, the groove height is between 0.05 and 1.0 mm, and preferably 0.1 to 0.3 mm.
[0067] The wet thickness of the coating controls the final cured film thickness. The wet thickness is affected by the final dry film thickness, the solids content of the coating, and the target porosity of the final dried film.
[0068] Wet thickness
[0069] In the above formula, DT is the final dry film thickness, which is controlled at 80-180nm, SC is the solid content of the coating, which is between 1% and 4.2%, and P is the target porosity, which is between 20-40%.
[0070] like Figure 2As shown, in the transmittance curve after sintering in which a sol-gel coating is coated on the surface of a glass substrate containing a tin layer, the spectrum is a relatively smooth curve in the 550-750 wavelength range, the overall thickness is relatively uniform, and the decline is relatively slow after 750, indicating that its weak light response performance is better.
[0071] like Figure 6 As shown in the figure, the structure of the dense layer on the surface can be seen in the electronic mirror scanning. There are no cracks or openings on the surface, which increases its weather resistance. It increases wear resistance and reduces the attenuation of the film layer. More importantly, the surface is relatively smooth, and the performance in dust and dust prevention is also improved. It reduces the later operation and maintenance costs and improves the power generation efficiency of the components.
[0072] The final dry film hardness is between 3H and 6H pencil hardness.
[0073] The wear resistance of the final dry film can perform abrasion tests 50 times according to the specification EN1096-2 method without losing 0.5% absolute transmittance loss measured by a spectrophotometer, and no marks after friction will be produced on the surface of the final dry film under 1000Lux lighting conditions. At the same time, after the glass substrate is turned 180°, the surface of the final dry film will not be affected by the transmission device.
[0074] like Figure 5 As shown, the final film thickness is calculated by the spectral curve and the refractive index of the sol-gel liquid, and the final film thickness is a function of the initial (before curing) dry film thickness and the curing parameters, so that the curing parameters can change the initial dry thickness, and the sol-gel coating is cured to a thickness of 80nm to 180nm, and preferably 120nm to 150nm, by Figure 5 Data for the sol-gel coatings in Figure 1 demonstrate the relationship between the maximum cure temperature and the final film thickness, refractive index, and water contact angle.
[0075] The thickness of the final dry film is affected by the curing process parameters, which include the glass substrate speed, the air temperature in the furnace, the heat radiation of the heating device, the distance from the heating device to the glass substrate and the set temperature. The final dry film is cured to a thickness of 80nm to 180nm by adjusting the curing parameters.
[0076] like Figure 3 and 4 As shown, the heating characteristics are mainly based on thermal radiation, and the energy radiated by the heating device is based on the logarithmic proportion of the Planck curve and the relationship between the radiation power and the wavelength;
[0077] According to Planck's theory, our radiation and absorption rate in the infrared spectrum band of 2.7-4.5 are in an ideal state. We can adjust the speed and beat according to the production capacity requirements, so that the solvent coated with sol-gel can reach the substrate temperature we need under various changes, achieve the drying and hardness of the film layer, and meet its wear resistance.
[0078] In S2, the hot air circulation device blows 30-50°C hot air evenly onto the glass surface through 3-8 groups of wind knives or 3-9 infrared heating systems with a gold-plated layer through the 2.7-4.5μm band, and dries and heats the glass substrate to 25-28°C based on the principle of thermal radiation. The temperature of the substrate needs to supplement heat to the elastic roller made of polyurethane with a surface hardness of 35-38 to increase the elasticity of the rubber roller.
[0079] In S9, the tempering performance of the glass substrate is controlled by a tempering sintering process. The process parameters of the tempering sintering include the movement of the glass substrate, the temperature of the furnace body, the heat radiation of the heating device, the cooling capacity of the high-pressure fan quenching process, and the overall cooling efficiency. The tempering performance of the glass substrate is controlled by adjusting the process parameters.
[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing anti-reflection glass coated on the surface of a tin layer, characterized in that: The steps for preparing the anti-reflection glass coated with a tin layer are as follows: S1, tin layer glass is put on, inspected and cleaned, and surface defects are detected; S2, preheating the tin layer glass substrate; S3, sol-gel coating; S4, subjecting the sol-gel coated on the surface of the glass substrate to surface tension shrinkage; S5, curing the sol-gel by infrared radiation or hot air circulation; S6, cooling and waste discharge; S7, turning the glass substrate 180°; S8, glazing the surface of the glass substrate; S9, tempering, quenching, cleaning and drying the glass substrate; In S3, the glass substrate is washed, cleaned and dried before entering a preheating device, and the glass substrate is sent to a combined roller coating device with a liquid flow trough, and the sol-gel solution is evenly coated on the glass substrate, and the glass substrate passes through a conveying area and a curing area to form a solid film layer with a porous structure and a dense surface; The flow tank is formed with a gel storage tank and a discharge tank, the bottom area of the gel storage tank is larger than the bottom area of the discharge tank, and the thickness of the sol-gel layer on the glass substrate is determined by the discharge rate of the fluid in the flow tank; The discharge flow rate V=Q / Lh, Q is the flow rate of sol-gel per unit time, L is the length of the tank, and h is the height of the tank; Flow rate Q = LΔPh 3 / 12wμ, L is the slot length, ΔP is the pressure difference across the slot width, ΔP=P1-P0, P0 is the pressure on the surface of the sol-gel solution, P1 is the pressure at the inlet of the discharge slot, h is the slot height, w is the slot width, and μ is the viscosity of the coating; The length of the inflow section between the parallel surfaces is calculated by the Braus approximation method, that is, the slot length L = hReH / 100, where h is the slot height, H is the fluid pressure head height, and Re is the Reynolds number of the coating fluid; The flow rate of the coating will also affect the internal pressure of the flow tank. If the flow rate is too high, the coating will not be able to fill the flow tank, so that the coating cannot be evenly distributed in the flow tank; if the flow rate is too low, the flow tank will be completely filled with coating, resulting in uneven flow rate and excessive back pressure. Therefore, the pressure difference between the glue tank and the discharge tank will affect the quality and uniformity of the coating. The pressure in the flow tank includes the pressure P0 on the surface of the sol-gel solution, the pressure P1 at the inlet to the discharge tank, and the pressure P2 at the outlet of the discharge tank. The pressure is also related to the fluid pressure head height H. AP=P1-P2, ΔP=ρgH+P0, because the pressure P0 on the surface of the sol-gel solution is the atmospheric pressure, therefore, Based on the above parameters and calculations, for sol-gel coatings, the groove height is between 0.05 and 1.0 mm.
2. The method for preparing an anti-reflection glass coated on the surface of a tin layer according to claim 1, characterized in that: The groove height is between 0.1 and 0.3 mm.
3. The method for preparing an anti-reflection glass coated on the surface of a tin layer according to claim 1, characterized in that: The wet thickness of the coating controls the final cured film thickness, which is affected by the final dry film thickness, the solids content of the coating, and the target porosity of the final dried film; Wet thickness In the above formula, DT is the final dry film thickness, which is controlled at 80-180nm, SC is the solid content of the coating, which is between 1% and 4.2%, and P is the target porosity, which is between 20-40%.
4. The method for preparing an anti-reflection glass coated on the surface of a tin layer according to claim 3, characterized in that: The hardness of the final dry film is between 3H and 6H in pencil hardness.
5. The method for preparing an anti-reflection glass coated on the surface of a tin layer according to claim 3, characterized in that: The final dry film can perform an abrasion test 50 times according to the specification EN1096-2 method without losing 0.5% of the absolute transmittance loss measured by a spectrophotometer, and no marks after friction will be produced on the surface of the final dry film under 1000 Lux lighting conditions. At the same time, after the glass substrate is flipped 180°, the surface of the final dry film will not be affected by the transmission device.
6. The method for preparing an anti-reflection glass coated on the surface of a tin layer according to claim 3, characterized in that: The thickness of the final dry film is 120 nm to 150 nm.
7. The method for preparing an anti-reflection glass coated on the surface of a tin layer according to claim 1, characterized in that: In S2, the hot air circulation device blows 30-50°C hot air evenly onto the glass surface through 3-8 groups of wind knives or 3-9 infrared heating systems with a gold-plated layer through the 2.7-4.5μm band, and dries and heats the glass substrate to 25-28°C based on the principle of thermal radiation. The temperature of the substrate needs to supplement heat to the elastic roller made of polyurethane with a surface hardness of 35-38 to increase the elasticity of the rubber roller.
Citation Information
Patent Citations
Device for forming aerosol, and method and apparatus for coating glass
CN102010138A
Antireflection coated glass with self-cleaning effect and preparation method thereof
CN102838288A
Coating and curing apparatus and methods
CN105209177A
Preheating method and equipment for coated glass production
CN111410434A
Tuning the Anti-reflective, abrasion resistance, Anti-soiling and self-cleaning properties of transparent coatings for different glass substrates and solar cells
US20140261673A1
